A Missed Opportunity: The Public Investigation into the Conduct of the RCMP in Matters Involving Nicole (Ryan) Doucet. Issue 1 (27th June 2017) - Chambers, Lori; Verrelli, Nadia
Abstract: On July 13, 2013, the Commission for Public Complaints released the Report Following a Public Interest Investigation into the Conduct of RCMP Members in Nova Scotia in Respect to Matters Involving Nicole (Ryan) Doucet . After interviewing all parties involved and reviewing 25 incidences involving Ms. Doucet and Mr. Ryan, the Acting Commissioner, Ian McPhail, concluded the RCMP's policy regarding violence in relationships "was followed at all times." According to The Report, the RCMP did not fail to protect Ms. Doucet. These conclusions, however, seem to be at odds with the evidence presented in The Report . After discussing coercive control and reviewing R. v. Ryan, the paper analyses the Commission's findings to argue that the evidence presented to the Commission clearly illustrates that police ignored Ms. Doucet's repeated pleas for help. The Commissioner missed a real opportunity to review current RCMP policies on domestic violence to bring them in line with current and on-going research on coercive control. Résumé: Le 13 juillet 2013, la Commission des plaintes du public contre la GRC publiait le Rapport produit à la suite d'une enquête d'intérêt public sur la conduite de membres de la GRC en Nouvelle-Écosse en lien avec l'affaire concernant Nicole (Ryan) Doucet. Au terme d'entrevues menées auprès de toutes les parties en cause, et d'une étude de 25 incidents impliquant M me Doucet et M. Ryan, le commissaire intérimaire, Ian McPhail, concluait que la politique de la GRC concernant la violence familiale « a été observée en tout temps ». D'après le Rapport, la GRC n'a pas failli dans son devoir de protéger M me Doucet. Toutefois, cette conclusion semble être contraire aux faits présentés dans le Rapport. Ayant abordé la notion de contrôle coercitif et examiné l'affaire R. c. Nicole (Ryan) Doucet, cet article analyse les conclusions de la Commission et affirme qu'au contraire, l'information présentée à la Commission prouve clairement que la police a fait la sourde oreille aux demandes d'aide répétées de M me Doucet, et que le commissaire a laissé passer une occasion en or de repenser les politiques de la GRC sur la violence familiale afin de les harmoniser avec les recherches actuelles et en cours sur le contrôle coercitif.